Wellness application, effects, and evaluation from the cardiofood lifestyle program: a latin american experience: Aplicación, efectos y evaluación del bienestar a partir del programa cardiofood lifestyle: una experiencia latinoamericana - Hasbani, Yael Alejandra (2021)
Introduction: The changes in daily routines as a result of the mitigating measures implemented in the face of the COVID-19 pandemic represent a challenge for the Latin American population to preserve their general well-being. Objective: To evaluate the wellness assessment from the lifestyle medicine program Cardiofood Lifestyle in virtual modality in Latin American participants during the COVID-19 pandemic in 2020. Methods: Analytical, retrospective and descriptive study, with a quantitative approach; developed in virtual mode between May and December 2020. The population sample was 51 participants. A subjective assessment questionnaire and a self-authorship wellness score were applied and validated by a hypothesis test. The P value equal to zero is calculated. Results: Of 51 participants, 44 (86%) were women with a mean age of 45 and 7 (14%) were men with a mean age of 40 years. The mean of the evaluation test of the Cardiofood Lifestyle program was 4.71. 35 (68.62%) participants felt more energetic; 46 (90%) expressed feeling much more secure in choosing healthy foods; 36 (70.58%) felt much more lucid and 41 (80.40%) stated that they felt much healthier compared to the beginning of the program. Conclusions: There is a good subjective wellness assessment represented in Latin American participants of the Cardiofood Lifestyle medicine program in virtual mode during the COVID-19 pandemic in 2020, represented in better sensations of energy, lucidity, ability to make food choices and health.